2021
DOI: 10.31235/osf.io/79dth
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Political trust as a cause and consequence of democracy: Longitudinal analysis of European data

Abstract: The causal link between political trust and democratic performance has been assumed rather than established. Building on research on political trust as related to regime legitimacy and on the evaluative nature of political trust, we formulate hypotheses about the effect of political trust on democracy and of democracy on political trust, both with regard to overall levels of trust in societies, as well as trust by education and age groups. We test these hypotheses with cross-lagged models applied to country ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Furthermore, we expect the relationship between policy opinion congruence and political trust to be contingent upon some characteristics that are specific to the individuals. Previous research has emphasised the impact of education levels in moderating the effect of the quality of democracy on political trust (Kolczynska & Bürkner, 2021) or satisfaction with democracy (Mayne & Hakhverdian, 2017). For instance, Mayne and Hakhverdian (2017) found that the effect of congruence on democratic satisfaction is larger for citizens with higher levels of education.…”
Section: Explaining the Effect Of Policy Opinion Congruence On Trust In The Parliamentmentioning
confidence: 99%
“…Furthermore, we expect the relationship between policy opinion congruence and political trust to be contingent upon some characteristics that are specific to the individuals. Previous research has emphasised the impact of education levels in moderating the effect of the quality of democracy on political trust (Kolczynska & Bürkner, 2021) or satisfaction with democracy (Mayne & Hakhverdian, 2017). For instance, Mayne and Hakhverdian (2017) found that the effect of congruence on democratic satisfaction is larger for citizens with higher levels of education.…”
Section: Explaining the Effect Of Policy Opinion Congruence On Trust In The Parliamentmentioning
confidence: 99%